2007
DOI: 10.1159/000109943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Muscle Cooling on the Stiffness of the Human Gastrocnemius Muscle in vivo

Abstract: Background/Aims: The effects of muscle cooling on the stiffness of the human gastrocnemius muscle (GAS) were examined in vivo. Methods: The knee joint was passively extended from 90 to 0° (0° = full knee extended position) with a constant ankle angle of 10° dorsiflexed position (0° = the sole of the foot is approximately perpendicular to the anterior margin of the shaft of the tibia) in a control condition (room temperature of 18–23°C) and a cooling condition (muscle temperature decreased by 5.8 ± 1.7°C after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
(57 reference statements)
2
19
2
1
Order By: Relevance
“…It must be taken into account that the viscosity of a tissue diminishes with elevated temperature and increases with cold. 44,45 This muscle response was described by Noonan et al 46 in rabbit skeletal muscles (tibialis anterior and extensor digitorum longus) and by Muraoka et al, 25 who analyzed the human gastrocnemius muscle after cooling in a cold-water bath at 5-CY8-C for 60 mins.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It must be taken into account that the viscosity of a tissue diminishes with elevated temperature and increases with cold. 44,45 This muscle response was described by Noonan et al 46 in rabbit skeletal muscles (tibialis anterior and extensor digitorum longus) and by Muraoka et al, 25 who analyzed the human gastrocnemius muscle after cooling in a cold-water bath at 5-CY8-C for 60 mins.…”
Section: Discussionmentioning
confidence: 83%
“…18Y20 The same effects have been proposed for agility, 20,21 velocity, 22 and neuromuscular function. 23 Other studies indicate that cold improves sport performance, 24,25 does not significantly alter performance, 26Y28 or does so in certain circumstances. 29 This study analyzes changes in muscle response of the dominant-leg vastus lateralis (VL) when subjected to four successive immersions (4 Â 4 mins) in water at 4-C.…”
mentioning
confidence: 99%
“…For example, it has been previously demonstrated that fatigue induced by repeated muscular contractions can cause temporary changes in the stiffhess properties ofthe muscle-tendon unit, Kubo et al, (19) reported that a repetitive isometric exercise was accompanied by a marked lengthening in electromechanical delay and an increase in tendon compliance. Further, in a group of well-trained runners, a reduction in both vertical and leg stiffiiess has been reported after a run test to exhaustion (7), In addition, fatigue caused by four periods of 30-s all-out sprint cycling exercise was demonstrated to lengthen electromeehanieal delay and reduce maximal isometric contraction and rate of force development in healthy men (36), Nonetheless, it must be recognized that the passive change in temperature alone has been solely shown to alter the stiffness characteristics of the tendon because of a rearrangement of the dense connective tissue, Speeifically, muscle cooling would cause an increase (28), whereas a rise in temperature would be responsible for a reduction in muscle-tendon stiffness (24), In contrast, repetitive drop jumps did not change the elongation characteristies of the tendon and aponeurosis ofthe knee extensor muscles (18), Other authors did not find a significant postfatigue alteration of vertical stiffness measured by a hopping test in physically active male and female subjects (30), It is clear that fatigue has noticeable effects on performance in a range of different tasks, and to the best of our knowledge, the effect of fatigue induced by a repetitive, concentric-only action such as cycling on the expression of MA stifi&iess is yet to be examined. Further, the relationship between initial MA stiffhess levels and the response to fatigue is also an area of enquiry that is yet to be investigated.…”
mentioning
confidence: 99%
“…On the other hand, short-term adverse effects on proprioception [7], neuromuscular performance [8], or changes in passive muscle stiffness have been discussed [9]. There is evidence for a significant increase of passive joint torque with a maximal range of motion (ROM) after CWI or application of ice-packs therapy [10][11][12]. Consequently, a higher mechanical stress is applied on the muscle-tendon unit, associated with a reduced capacity of the muscle to withstand active or passive stretch or rather increased muscle stiffness [9].…”
Section: Introductionmentioning
confidence: 99%